(untitled) (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2020)
This study aims to (1) describe and analyze the condition of existing apparatus resources in the Merauke Regency Regional Personnel Agency; and (2) describe and analyze the apparatus development strategy in the Merauke Regency Regional Personnel Agency. This research applies a qualitative approach. The informants involved included: (1) Head of the Regional Civil Service Agency; (2) Subdivision of the Strategy of the Regional Civil Service Agency Resources; and (3) a number of training alumni employees. Data collection techniques are interviews, observation, study of literature and documentation. Data analysis techniques are carried out through data reduction, data presentation and data verification. The results showed that the implementation of education and training, especially in the Merauke Regency Regional Personnel Agency, had been effective, although there were still some improvements that needed to be made so that the results of the training could be maximized as expected. Employees are the most important resource in a public organization. Good employees who meet the qualification standards can only be obtained through effective recruitment efforts. The implementation of education and training in the Merauke Regency Regional Personnel Agency is good because based on the results it shows starting from training materials, good and effective delivery methods in the training process, facilities and infrastructure to support training activities, skilled presenters, learning process according to standard procedures, proportion of time and the method of implementation was working well and effectively.